2002
DOI: 10.1046/j.1467-789x.2002.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic obesity in humans: what do we know and what can be done?

Abstract: Obesity is a common sequel to tumours of the hypothalamic region and their treatment with surgery and radiotherapy. The prevalence of hypothalamic obesity has been underestimated because it may take some years to develop, and the problem has been under-recognized by physicians. Weight gain results from damage to the ventromedial hypothalamus which leads, variously, to hyperphagia, a low metabolic rate, autonomic imbalance, growth hormone (GH) deficiency and various other problems that contribute to weight gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 61 publications
3
38
0
2
Order By: Relevance
“…It relates mostly to patients treated for hypothalamic-pituitary tumors [8,14,[20][21][22]. As far as some authors are concerned, hypothalamic obesity may develop even some years after hypothalamic tumors management [22], though there are observations that first symptoms may be present shortly after surgery [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It relates mostly to patients treated for hypothalamic-pituitary tumors [8,14,[20][21][22]. As far as some authors are concerned, hypothalamic obesity may develop even some years after hypothalamic tumors management [22], though there are observations that first symptoms may be present shortly after surgery [23].…”
Section: Discussionmentioning
confidence: 99%
“…Meuric et al [24] evaluated patients with craniopharyngioma after extensive treatment and primary damage of hypothalamus and observed correlation between weight gain and increased insulin secretion. Hyperinsulinemia can develop either before the surgical treatment or after completed therapy [21][22][23][24][25]. The cause of increased insulin concentration in the serum indirectly explained animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…124,125 Sibutramine might be useful in obese adolescents. 17,[126][127][128][129][130][131] In an early placebo-controlled trial in 82 obese adolescents receiving behavior therapy and sibutramine (starting dose 5 mg/day and uptitrated to 15 mg/day) the authors demonstrated a weight reduction significantly higher in the sibutramine group than in the placebo group (by 4.6 kg) after six months. 17 All participants received sibutramine for the following six months.…”
Section: The Case Of Childhood Obesitymentioning
confidence: 99%
“…Hyperphagia and obesity are common sequelae of tumours of the hypothalamic region and their treatment with surgery and radiotherapy [11]. Damage to the ventromedial hypothalamus leads to hyperphagia, a low metabolic rate, growth hormone (GH) deficiency and autonomic imbalance that contribute to weight gain [11].…”
Section: Disorders Of Appetite In Physical Illnessmentioning
confidence: 99%
“…Damage to the ventromedial hypothalamus leads to hyperphagia, a low metabolic rate, growth hormone (GH) deficiency and autonomic imbalance that contribute to weight gain [11]. However, with the exception of GH replacement, few clinical trials have evaluated significant numbers of patients and their management by behavioural, dietary, pharma-cological and surgical approaches [11].…”
Section: Disorders Of Appetite In Physical Illnessmentioning
confidence: 99%